GAMBARAN KESEJAHTERAAN SUBJEKTIF LANSIA YANG AKTIF DALAM KEGIATAN RELIGIUS - Novi Kosalina (Psibernetika, 2018)
There were images that older adults are predominantly senile, unproductive, poor in health, and useless. In fact, there are many older adults who still optimally function, such as on religious activities. Religious activities give positive impact for these older adults life. Having social support from religious community and give sense of meaning and purpose. Older adults can have subjective wellbeing, which can decrease depression risk and health problems. Subjective wellbeing is evaluation about one’s happiness, on emotional, psychological, and social aspect. This research was conducted as an effort to understanding in much deeper and more comprehensive way about subjective wellbeing in older adults who is active in religious activities.  There are four subjects that involved in this research. They were 67-77 years old, widowed, and active in religious activities. This research is using interview method, conducted in about one month. Results indicate that all subjects have subjective wellbeing. Keyword: Older Adults, Subjective Well-Being, Religious Activities